2018
DOI: 10.18632/oncotarget.26055
|View full text |Cite
|
Sign up to set email alerts
|

A safety study of newly generated anti-podoplanin-neutralizing antibody in cynomolgus monkey (Macaca fascicularis)

Abstract: Hematogenous metastases are enhanced by platelet aggregation induced by tumor cell-platelet interaction. Podoplanin is a key molecule to enhance the platelet aggregation and interacts with C-type lectin-like receptor 2 (CLEC-2) on platelet via PLAG domains. Our previous reports have shown that blocking podoplanin binding to platelets by neutralizing antibody specific to PLAG4 domain strongly reduces hematogenous metastasis. However, podoplanin is expressed in a variety of normal tissues such as lymphatic vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…5,23 Among our identified PLAG domains, the fourth PLAG domain (PLAG4) in human PDPN (hPDPN) was found to play an important role in CLEC-2 binding and platelet aggregation. 23,28 The amino acid sequence alignment in mouse and human revealed that mouse PDPN (mPDPN) had a similar consensus motif (82-EELST-86) to human PLAG4 (81-EDLPT-85; Figure 1A, see Supplemental materials and methods). To evaluate the contributions of each mouse PLAG domain to CLEC-2 binding, we established CHO cells expressing PLAG domain-deleted mPDPN mutants (CHO/mPDPN-ΔPLAG1, -ΔPLAG3, -ΔPLAG4, -ΔPLAG1+4, -ΔPLAG3+4, and -ΔPLAG1+3+4; Figure 1B) and assessed their binding abilities to recombinant mouse CLEC-2 (mCLEC-2).…”
Section: Critical Role Of the Mouse Plag4 Domain In Clec-2 Binding And Platelet Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…5,23 Among our identified PLAG domains, the fourth PLAG domain (PLAG4) in human PDPN (hPDPN) was found to play an important role in CLEC-2 binding and platelet aggregation. 23,28 The amino acid sequence alignment in mouse and human revealed that mouse PDPN (mPDPN) had a similar consensus motif (82-EELST-86) to human PLAG4 (81-EDLPT-85; Figure 1A, see Supplemental materials and methods). To evaluate the contributions of each mouse PLAG domain to CLEC-2 binding, we established CHO cells expressing PLAG domain-deleted mPDPN mutants (CHO/mPDPN-ΔPLAG1, -ΔPLAG3, -ΔPLAG4, -ΔPLAG1+4, -ΔPLAG3+4, and -ΔPLAG1+3+4; Figure 1B) and assessed their binding abilities to recombinant mouse CLEC-2 (mCLEC-2).…”
Section: Critical Role Of the Mouse Plag4 Domain In Clec-2 Binding And Platelet Activationmentioning
confidence: 99%
“…Each sample was treated with a previously described procedure. 28 Samples were incubated with primary antibodies to PDPN (mouse anti-human PDPN mAbs, PG4D1 and PG4D2; Syrian hamster anti-mouse PDPN mAb, ab11936, Abcam) and β-actin (clone, AC-15; Sigma-Aldrich), treated with HRP-conjugated anti-mouse IgG (RPN2232, GE Healthcare), anti-hamster IgG (57003, Cappel), and mouse TrueBlot ULTRA (18-8817-33, Rockland), and then reacted with an ECL Prime Western Blotting Detection reagent (GE Healthcare). The proteins were visualized with enhanced chemiluminescence using Amersham Imager 600 (GE Healthcare).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…In addition to OSCC, PDPN promotes a variety of other cancers including mammary carcinoma [ 62 , 63 ], glioma [ 64 67 ], melanoma [ 59 , 68 , 69 ], ovarian cancer [ 70 ], and pulmonary adenocarcinoma [ 71 73 ]. Indeed, PDPN has been identified as an enticing target for chemotherapy [ 74 , 75 ]. The roles of cadherins and PDPN in contact normalization described in this study should yield insight into fundamental mechanisms that affect the general process of cancer development and progression at the cellular level of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-human PDPN mAb NZ-1, which recognizes the PLAG2/3 domain, has a neutralizing activity in relation to the PDPN-CLEC-2 interaction and inhibits PDPN-induced platelet aggregation and hematogenous lung metastasis [16,66] (Figure 1). Other anti-PDPN mAbs, P2-0 [152] and MS-1 [153] also recognize the PLAG2/3 domain, and 2F7 [154] recognizes the PLD/PLAG4 domain. These mAbs also suppress platelet aggregation and hematogenous pulmonary metastasis by inhibiting CLEC-2 interaction.…”
Section: Anti-pdpn Monoclonal Antibodies (Mabs)mentioning
confidence: 99%